Magnetic Field Finite Element Analysis of Disc-type Magnetorheological Fluid Transmission Device Driven by Shape Memory Alloy - Huang Jin; Qiao Zhen (Jixie chuandong)
The disc- type magnetorheological fluid transmission device driven by shape memory alloy under thermal effect is a transmission device that its output speed rapidly changes with the temperature changes.Compared with the clutch working with high temperature,the transmission device extends the service life of the magnetorheological fluid. Aiming at transmission device,the working principle is analyzed,the magnetic circuit theoretical model is established based on Ohm’s law of magnetic circuit. The magnetic circuit theoretical model of transmission device is simulated by ANSYS software and the correctness of the simulation model is verified by the iterative calculation. The influences of different disc material and working gap size along the radial magnetic induction intensity are obtained by simulation of magnetic circuit,moreover the influence of isolation ring to the magnetic field intensity and output torque is analyzed.